Turning ordinary love into extraordinary outcomes at East Park - Liam Feeney (Scottish Journal of Residential Child Care, 2020)
This article describes East Park School’s journey in conceptualising agape and what it means to provide a care experience that demonstrates love in a meaningful way:- Explaining why young people need to feel loved and not just cared for.- Describing how we explored the difficulties of maintaining professional boundaries in practice, while managing risk in situations where we looked for more loving ways to intervene.- Showing how we build on trust and existing relationships to create more opportunities for our young people to experience love.- Defining what love means to young people with complex and multiple diagnoses and witnessing extraordinary outcomes.- Explaining how we entrench the expectation of love into recruitment and induction conversations for new staff.